Immobilization of TiO2 with cement: photocatalytic degradation of phenol and its kinetic studies - Sopyan, Iis; Hafizah, Nor; Jamal, Parveen (National Institute of Science Communication and Information Resources (CSIR), 2011)
Two types of TiO2 powders with water - to - titanium tetraisopropoxide (TPT) ratios of 1 (Powder 1) and 2 (Powder 2) were synthesized via sol-gel method. Both powders were characterized physicochemically before immobilized with white plaster cement for photodegradation of phenol in liquid phase. Aqueous phenol solution containing cement-bonded of TiO2 Powders 1 and 2 were irradiated with UV light of 2.6 mW/cm2 intensity and their efficiency was compared using Langmuir-Hinshelwood kinetic model. From the kinetic analysis, it was found that the adsorption equilibrium constant (KLH) of Powder 1 was higher than that of Powder 2 due to higher specific surface area. Powder 2 has higher value of the reaction rate constant (kr) as its high crystallinity was capable to generate better charge separation to destruct phenol molecules on its surface.